The Role of Customer Satisfaction in Mediating Service Quality, Atmosphere, and Price Perception on Revisit Intention - Eka Pratiwi, Putu Melinia Sri; Oka Martini, Ida Ayu Sri (Universitas KH. Abdul Chalim Mojokerto, 2026)
Bali, as one of the world’s leading tourist destinations, continues to record significant growth in visitor arrivals, in line with the rising popularity of new attractions such as beach clubs that have become favorite destinations among tourists. This study aims to examine the influence of service quality, atmosphere, and perceived price on revisit intention, with customer satisfaction acting as a mediating variable. A quantitative research design was applied, involving 100 respondents, and the data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The results show that service quality, atmosphere, and perceived price have a positive effect on both customer satisfaction and revisit intention. Furthermore, customer satisfaction was found to mediate the relationship between the three independent variables and revisit intention. These findings emphasize the importance of providing high-quality services, creating a comfortable atmosphere, and offering reasonable prices in order to enhance satisfaction and encourage revisit intention. The study offers strategic implications for beach club managers and tourism stakeholders in improving repeat visits on a sustainable basis.